Solid acid catalyst and preparation method thereof, and hydroxybutyl acrylate compound and preparation method thereof

By using a solid acid catalyst to catalyze the ring-opening addition reaction between acrylic compounds and tetrahydrofuran, the problem of high selectivity of by-product polytetrahydrofuran is solved, and the product selectivity of hydroxybutyl acrylate compounds and the catalyst recovery efficiency are improved.

CN119456023APending Publication Date: 2025-02-18WANHUA CHEM GRP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411715150.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, when preparing hydroxybutyl acrylate compounds, the by-product polytetrahydrofuran has high selectivity, which affects the purity and selectivity of the product.

Method used

A solid acid catalyst is used, which consists of a bonding material, a tin-doped molecular sieve support and an acid, including silicoblastic acid and an inorganic acid, for catalyzing the ring-opening addition reaction of acrylic compounds with tetrahydrofuran.

Benefits of technology

It improves the conversion rate of tetrahydrofuran, reduces its self-polymerization, reduces the selectivity of polytetrahydrofuran, improves the product selectivity of hydroxybutyl acrylate compounds, and has no catalyst waste liquid, and the catalyst and product are easily separated, which is conducive to catalyst recovery. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of catalytic synthesis, in particular to a solid acid catalyst and a preparation method thereof as well as a hydroxybutyl acrylate compound and a preparation method thereof. The solid acid catalyst comprises a binding material, a tin-doped molecular sieve carrier and acid, the tin-doped molecular sieve carrier is dispersed in the binding material and is loaded with the acid, and the acid comprises silicomolybdic acid and inorganic acid. The solid acid catalyst provided by the invention can be applied to catalysis of a ring-opening addition reaction of an acrylic acid compound and tetrahydrofuran, has moderate catalytic activity, and is beneficial to improvement of the conversion rate of tetrahydrofuran, reduction of self-polymerization of tetrahydrofuran, reduction of the selectivity of polytetrahydrofuran and improvement of the product selectivity of a hydroxybutyl acrylate compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of catalytic synthesis, and in particular to a solid acid catalyst and a preparation method thereof, and a hydroxybutyl acrylate compound and a preparation method thereof. Background Art

[0002] Hydroxybutyl acrylate compounds are a special type of acrylic ester monomers with long-chain ester groups in their molecular structure, and the ends of the long-chain ester groups carry hydroxyl groups, which have the potential to play special functions in polymerization reactions. For example, they can react with isocyanate compounds or acid compounds to form a cross-linked structure, improving the physical properties of the polymer, such as flexibility, warping resistance, scratch resistance, and chemical resistance. In addition, compared with short-chain hydroxyl-type acrylates, the long-chain ester groups of hydroxybutyl acrylate compounds increase the reaction freedom of the hydroxyl group, making it exhibit better performance in the cross-linking reaction, better cross-linking quality, and a higher degree of freedom in the formed structure. At present, hydroxybutyl acrylate compounds are mainly used as components of adhesives for the preparation of glues, inks, coatings, etc.

[0003] At present, there are two methods for preparing hydroxybutyl acrylate compounds: direct esterification and transesterification. The direct esterification method mainly uses acrylic acid compounds and 1,4-butanediol to react under acidic catalyst conditions, and the transesterification method uses acrylic acid compound methyl ester and 1,4-butanediol to react under transesterification catalyst conditions. However, the above methods need to consider the treatment plan of by-products (such as methanol).

[0004] Hydroxybutyl acrylate compounds can also be generated through the ring-opening addition of acrylic compounds and tetrahydrofuran. However, during the ring-opening addition process, tetrahydrofuran is prone to self-polymerization to produce by-product polytetrahydrofuran, and the product selectivity of hydroxybutyl acrylate compounds is low. Summary of the invention

[0005] Based on this, the first aspect of the present application provides a solid acid catalyst, and its technical solution is as follows:

[0006] A solid acid catalyst comprises a bonding material, a tin-doped molecular sieve carrier and an acid. The tin-doped molecular sieve carrier is dispersed in the bonding material and loaded with an acid, wherein the acid comprises silicomolybdic acid and an inorganic acid.

[0007] The solid acid catalyst provided in the present application can be used to catalyze the ring-opening addition reaction of acrylic acid compounds and tetrahydrofuran, has moderate catalytic activity, is beneficial to improving the conversion rate of tetrahydrofuran, reducing the self-polymerization of tetrahydrofuran, reducing the selectivity of polytetrahydrofuran, and improving the product selectivity of hydroxybutyl acrylate compounds.

[0008] Furthermore, after the solid catalyst is used to catalyze the ring-opening addition reaction of acrylic acid compounds and tetrahydrofuran, there is no catalyst waste liquid, and the catalyst and the product are easily separated, which is beneficial to the recovery of the catalyst.

[0009] In some embodiments, the mass percentage of the silicomolybdic acid in the solid acid catalyst is 10wt% to 50wt%. For example, the mass percentage is 10wt%, 20wt%, 30wt%, 40wt%, 50wt%. Preferably, it is 25wt% to 40wt%.

[0010] In some embodiments, the mass percentage of the inorganic acid in the solid acid catalyst is 3 wt % to 5 wt %, for example, 3 wt %, 4 wt %, or 5 wt %.

[0011] In some embodiments, the inorganic acid comprises one or more of nitric acid, hydrochloric acid, sulfuric acid and phosphoric acid. Preferably, the inorganic acid comprises sulfuric acid.

[0012] Wherein, the bonding material is formed by bonding agent molding, and the bonding agent includes one or more of pseudo-boehmite, silica sol and alumina sol. Optionally, the bonding agent includes pseudo-boehmite, silica sol and alumina sol, and the mass ratio of the pseudo-boehmite, silica sol and alumina sol is (8-10): (0.5-1.5): (0.5-1.5). Preferably, the mass ratio is (8-10): (0.8-1.2): (0.8-1.2). Preferably, the mass ratio is (8-10): 1:1.

[0013] In some embodiments, the solid acid catalyst is spherical. Optionally, the average particle size of the solid acid catalyst is 3 mm to 5 mm. The solid acid catalyst with the above particle size can be used as a filler in a reactive distillation tower.

[0014] In some embodiments, the mass percentage of tin in the tin-doped molecular sieve carrier is 3% to 8%. For example, the mass percentage is 3%, 4%, 5%, 6%, 7%, 8%. Preferably, it is 4% to 5%.

[0015] In some embodiments, the specific surface area of ​​the tin-doped molecular sieve carrier is 300 m 2 / g~500m 2 / g. For example, the specific surface area is 300m 2 / g, 400m 2 / g、500m 2 / g.

[0016] In some embodiments, the pore size of the tin-doped molecular sieve carrier is 0.3 μm to 0.5 μm, for example, the pore size is 0.3 μm, 0.4 μm, or 0.5 μm.

[0017] In some embodiments, the method for preparing the tin-doped molecular sieve carrier comprises the following steps:

[0018] The molecular sieve, water-soluble tin salt and water are mixed to allow tin ions to enter the molecular sieve, and the solid is collected for a first calcination treatment.

[0019] In some embodiments, mixing a molecular sieve, a water-soluble tin salt and water to allow tin ions to enter the molecular sieve comprises the following steps:

[0020] dissolving the water-soluble tin salt in the water to obtain a tin salt solution;

[0021] The molecular sieves are immersed in a plurality of the tin salt solutions respectively.

[0022] Optionally, the molecular sieve is selected from 4A molecular sieve.

[0023] Optionally, the water-soluble tin salt includes one or more of stannous sulfate and stannous chloride. Optionally, the tin salt includes stannous sulfate and stannous chloride. Optionally, the molar ratio of the stannous sulfate to the stannous chloride is (1-4):1. Preferably, it is (2-3):1.

[0024] Optionally, the amount, immersion time and immersion temperature of the tin salt solution are controlled so that the mass percentage of the tin element in the tin-doped molecular sieve carrier is 3% to 8%.

[0025] Optionally, the number of the tin salt solutions is 3 to 5.

[0026] Optionally, the total immersion time of the molecular sieve in the tin salt solution is 15 hours to 40 hours. Optionally, the immersion time of each time is 5 hours to 8 hours.

[0027] Optionally, the ambient temperature of the molecular sieve immersed in the tin salt solution is 20°C to 30°C.

[0028] After the molecular sieve is taken out from the last portion of the tin salt solution, the process further includes the steps of washing and drying the molecular sieve.

[0029] Optionally, the washing is performed 2 to 3 times, and in each washing, the mass ratio of water to the tin-containing molecular sieve is (1 to 10): 1. Preferably, it is (5 to 7): 1. The washing time for each washing is 1 hour to 2 hours. The washing temperature for each washing is 20° C. to 30° C.

[0030] Optionally, the drying temperature is 90° C. to 100° C., the drying pressure is 10 kPaA to 20 kPaA, and the drying time is 10 h to 20 h.

[0031] After drying, the solid is subjected to a first calcination treatment.

[0032] Optionally, the temperature of the first calcination treatment is 300°C to 400°C.

[0033] Optionally, the pressure of the first calcination treatment is 90 kPaA~95 kPaA.

[0034] Optionally, the first calcination treatment is performed for 5 h to 10 h.

[0035] The second aspect of the present application provides a method for preparing a solid acid catalyst, and its technical scheme is as follows:

[0036] A method for preparing a solid acid catalyst comprises the following steps:

[0037] loading silicomolybdic acid onto the tin-doped molecular sieve carrier to obtain a powder catalyst;

[0038] The powder catalyst, binder and inorganic acid are mixed, and after forming, a third calcination treatment is performed.

[0039] In some embodiments, loading silicomolybdic acid onto the tin-doped molecular sieve carrier comprises the following steps:

[0040] Mixing the tin-doped molecular sieve carrier, ammonium molybdate, ammonium silicate and water, stirring to obtain a mixed system;

[0041] The pH value of the mixed system is adjusted to react and generate the molybdenum silicate, and the solid is collected and subjected to a second calcination treatment.

[0042] Optionally, the ratio of the mass of the tin-doped molecular sieve carrier to the sum of the masses of the ammonium molybdate and the ammonium silicate is 1:(300-400). For example, the ratio is 1:300, 1:350, or 1:400.

[0043] Optionally, the molar ratio of ammonium molybdate to ammonium silicate is (1-2):1. For example, the molar ratio is 1:1, 1.5:2, 1:1. Preferably, it is (1-1.2):1.

[0044] Optionally, the temperature of the mixed system is adjusted to a pH value of 1 to 3. For example, the pH value is 1, 2, or 3.

[0045] Optionally, the method of adjusting the temperature of the mixed system to a pH value comprises: adding an inorganic acid to the mixed system. Optionally, the inorganic acid comprises one or more of nitric acid, hydrochloric acid, sulfuric acid and phosphoric acid. Preferably, the inorganic acid comprises sulfuric acid.

[0046] Optionally, the stirring temperature is 80° C. to 90° C. For example, the stirring temperature is 80° C., 85° C., or 90° C.

[0047] Optionally, the stirring time is 10 h to 15 h. For example, the stirring time is 10 h, 11 h, 12 h, 13 h, 14 h, or 15 h.

[0048] Optionally, the reaction temperature is 20° C. to 30° C. For example, the reaction temperature is 20° C., 25° C., or 30° C.

[0049] Optionally, the reaction time is 4 h to 8 h. For example, the reaction time is 4 h, 5 h, 6 h, 7 h, or 8 h.

[0050] After the reaction is completed, the steps of filtering and drying are also included.

[0051] Optionally, the filtration temperature is 20°C to 30°C and the pressure is 20kPaA to 30kPaA.

[0052] Optionally, the drying temperature is 80°C to 90°C, the drying pressure is 10kPaA to 20kPaA, and the drying time is 12h to 24h.

[0053] The dried solid is subjected to a second calcination treatment.

[0054] Optionally, the temperature of the second calcination treatment is 300°C to 400°C.

[0055] Optionally, the pressure of the second calcination treatment is 90 kPaA~95 kPaA.

[0056] Optionally, the second calcination treatment time is 5h~10h.

[0057] The obtained powder catalyst has a small particle size and is subjected to molding treatment, such as granulation molding.

[0058] Optionally, the binder includes one or more of pseudo-boehmite, silica sol and alumina sol; Optionally, the binder includes pseudo-boehmite, silica sol and alumina sol, and the mass ratio of the pseudo-boehmite, silica sol and alumina sol is (8-10): (0.5-1.5): (0.5-1.5). Preferably, the mass ratio is (8-10): (0.8-1.2): (0.8-1.2). Preferably, the mass ratio is (8-10): 1:1.

[0059] Optionally, the mass ratio of the powder catalyst, the binder and the sulfuric acid is (10-20): (1.5-4): (0.8-1.2). For example, the mass ratio is (10-20): (1.5-4): 1. Preferably, the mass ratio is (10-20): (2-3): 1.

[0060] Optionally, the temperature for mixing the powder catalyst, binder and inorganic acid is 30° C. to 40° C. Optionally, the time for mixing the powder catalyst, binder and inorganic acid is 8 h to 10 h.

[0061] Optionally, the intermediate product obtained by molding is spherical. Optionally, the average particle size of the intermediate product obtained by molding is 3mm~5mm.

[0062] After forming, a third calcination process is performed.

[0063] Optionally, the temperature of the third calcination treatment is 400°C to 500°C.

[0064] Optionally, the pressure of the third calcination treatment is 90 kPaA~95 kPaA.

[0065] Optionally, the third calcination treatment takes 4 to 8 hours.

[0066] The solid acid catalyst prepared by the method can be used to catalyze the ring-opening addition reaction of acrylic acid compounds and tetrahydrofuran, has moderate catalytic activity, is beneficial to improving the conversion rate of tetrahydrofuran, reducing the self-polymerization of tetrahydrofuran, reducing the selectivity of polytetrahydrofuran, and improving the product selectivity of hydroxybutyl acrylate compounds. After the solid catalyst is used to catalyze the ring-opening addition reaction of acrylic acid compounds and tetrahydrofuran, there is no catalyst waste liquid, the catalyst and the product are easily separated, and it is beneficial to catalyst recovery.

[0067] The third aspect of the present application provides a method for preparing hydroxybutyl acrylate compounds, and the technical scheme thereof is as follows:

[0068] A method for preparing a hydroxybutyl acrylate compound comprises the following steps:

[0069] In the presence of the solid acid catalyst as described above, the acrylic acid compound and tetrahydrofuran undergo a ring-opening addition reaction to generate the hydroxybutyl acrylate compound.

[0070] Optionally, the acrylic compound is selected from one or more of acrylic acid and 2-methyl methacrylate. When the acrylic compound is acrylic acid, the solid catalyst can catalyze a ring-opening addition reaction between it and tetrahydrofuran to generate 4-hydroxybutyl acrylate. When the acrylic compound is 2-methacrylic acid, the solid catalyst can catalyze a ring-opening addition reaction between it and tetrahydrofuran to generate 2-methyl methacrylate-4-hydroxybutyl ester.

[0071] Optionally, the tetrahydrofuran participates in the ring-opening addition reaction in a gaseous state. Compared with tetrahydrofuran participating in the ring-opening addition reaction in a liquid state, participating in the ring-opening addition reaction in a gaseous state is more conducive to reducing the selectivity of by-product polytetrahydrofuran.

[0072] The above ring-opening addition reaction can be carried out in a distillation coupled reactor, and tetrahydrofuran can participate in the reaction in a gaseous state. Figure 1 , is a schematic diagram of a preparation device for hydroxybutyl acrylate compounds according to an embodiment, wherein the preparation device 100 includes a reaction distillation tower 10, wherein the side wall of the reaction distillation tower 10 includes a first feed port 11 and a second feed port 12, and the first feed port 11 is higher in the gravity direction than the second feed port 12. The first feed port is used for feeding acrylic compounds, and the second feed port is used for feeding gaseous tetrahydrofuran. The reaction distillation tower 10 between the first feed port 11 and the second feed port 12 is loaded with the above-mentioned solid catalyst as a distillation filler. After the reactants are introduced, the gaseous tetrahydrofuran and the liquid acrylic compounds react in the loading section of the reaction distillation tower 10 where the solid catalyst is located to generate hydroxybutyl acrylate compounds. The molecular distance between gaseous tetrahydrofuran molecules is large, and the selectivity of self-polymerization to generate polytetrahydrofuran is greatly reduced, and the selectivity of the main product hydroxybutyl acrylate compounds is high.

[0073] Optionally, a condenser 20 is further included, one end of which is connected to the top of the reaction distillation tower 10, and the other end of which is connected to the second feed port 12. At this time, the condenser 20 is used to condense the tetrahydrofuran gas flowing out from the top of the reaction distillation tower 10, and recycle it into the reaction distillation tower 10 to continue to participate in the reaction.

[0074] Optionally, a short-path evaporator 30 is further included, and the short-path evaporator 30 includes a top inlet 31, a top outlet 32 ​​and a bottom outlet 33, the top inlet 31 is connected to the bottom of the reaction distillation tower 10, the top outlet 32 ​​is connected to the first feed port 11, and the bottom outlet is used for discharging. At this time, the short-path evaporator 30 is used to receive the material that will flow out from the bottom of the reaction distillation tower 10, and separate the acrylic acid compound from the hydroxybutyl acrylate compound, and recycle the acrylic acid compound into the reaction distillation tower 10 to continue to participate in the reaction, and the hydroxybutyl acrylate compound flows out.

[0075] Optionally, nitrogen is introduced into the reaction distillation tower 10 to control the tower top pressure to 0.1 MPaG-0.2 MPaG. The oil bath temperature is adjusted to maintain the tower top temperature at 90°C-100°C. Optionally, the pressure of the short-path evaporator is 1 kPaA-2 kPaA, and the oil bath temperature is 80°C-120°C.

[0076] Optionally, the molar ratio of the acrylic acid compound to tetrahydrofuran is (1-3):1. Preferably, it is (1.1-1.5):1.

[0077] Optionally, the ring-opening addition reaction is also carried out in the presence of a polymerization inhibitor, which is beneficial to further reduce the selectivity of polytetrahydrofuran. The polymerization inhibitor can be mixed with the acrylic acid compound and added into the reaction distillation vessel 10 through the first feed port 11.

[0078] Optionally, the mass ratio of the polymerization inhibitor to the acrylic compound is (0.001-0.005):1. Preferably, it is (0.002-0.003):1. Optionally, the polymerization inhibitor is selected from one or more of ZJ-701, ZJ-705, ZJ-706 and ZJ-709.

[0079] The method has low selectivity for polytetrahydrofuran, high selectivity for hydroxybutyl acrylate compounds, high atom economy, can be produced continuously, and no wastewater is generated in the whole process, which is green and environmentally friendly. After catalyzing the ring-opening addition reaction of acrylic acid compounds and tetrahydrofuran, no catalyst waste liquid is generated, and the catalyst and the product are easily separated, which is conducive to catalyst recovery.

[0080] The fourth aspect of the present application provides a hydroxybutyl acrylate compound, which is prepared by the preparation method as described above. The hydroxybutyl acrylate compound has a high purity. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0082] Figure 1 This is a schematic diagram of a device for preparing hydroxybutyl acrylate compounds. DETAILED DESCRIPTION

[0083] The present application will be further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.

[0084] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0085] the term

[0086] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0087] In the present application, "plurality", "multiple", "multiple times", "plurality", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0088] In the present application, “several” means at least one, such as one, two, etc., unless otherwise clearly defined.

[0089] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0090] In this application, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0091] In the present application, when referring to a numerical interval (i.e., a numerical range), unless otherwise specified, the optional numerical distribution within the above numerical interval is deemed to be continuous and includes the two numerical endpoints of the numerical range (i.e., the minimum value and the maximum value), and every numerical value between the two numerical endpoints.

[0092] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0093] In the present application, %(w / w) and wt% both represent weight percentage, %(v / v) refers to volume percentage, and %(w / v) refers to mass volume percentage.

[0094] In the present application, the specific surface area and pore size of the tin-doped molecular sieve carrier and the average particle size of the solid acid catalyst are measured by a physical adsorption instrument, and the instrument manufacturer and model are: MICROMERITICS (USA) ASAP2020.

[0095] In the present application, the mass percentage of the tin element in the tin-doped molecular sieve carrier is measured by an atomic spectroscopic absorption spectrometer, and the instrument manufacturer and model are: Perlin Elmer (USA), PinAACLE 900T.

[0096] In the present application, the mass percentage of sulfuric acid in the solid acid catalyst in the tin-doped molecular sieve carrier is analyzed and determined by a sulfur-chlorine analyzer, and the instrument manufacturer and model are: Jiangyan Hi-Tech, ZWK-2001.

[0097] In the present application, the mass percentage of silicomolybdic acid in the solid acid catalyst in the tin-doped molecular sieve carrier is determined by liquid chromatography analysis, and the liquid chromatography analysis uses a correction factor method. The instrument manufacturer and model: Shimadzu LC-2030.

[0098] In the present application, the masses of tetrahydrofuran and 4-hydroxybutyl acrylate are determined by gas chromatography analysis using a correction factor method, and the instrument manufacturer and model is Shimadzu 1020-plus.

[0099] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0100] Among them, 4A molecular sieve comes from Langfang Naco New Materials Technology Co., Ltd., industrial grade; stannous sulfate comes from Shandong Xinghai Chemical Co., Ltd., industrial grade; stannous chloride comes from Zhengzhou Yuteng Chemical Products Co., Ltd., industrial grade; ammonium molybdate comes from Henan Paiguang Chemical Products Co., Ltd., industrial grade; ammonium silicate comes from Dixin Chemical Co., Ltd., analytical grade; pseudo-boehmite comes from Yangzhou Zhongtianli New Materials Co., Ltd., industrial grade; silica sol comes from Linyi Kehan ​​Silicon Products Co., Ltd., industrial grade; aluminum sol comes from Harbin Yinyi Technology Co., Ltd., industrial grade; sulfuric acid comes from Beijing Inokai Technology Co., Ltd., analytical grade; acrylic acid comes from Wanhua Chemical Group Co., Ltd., industrial grade; methacrylic acid comes from Wanhua Chemical Group Co., Ltd., industrial grade; tetrahydrofuran comes from Beijing Inokai Technology Co., Ltd., analytical grade; ZJ-709 inhibitor comes from Anhui Liansheng New Materials Technology Co., Ltd., industrial grade. Strong acid cation exchange resin, brand A45, comes from Dow Chemical (Shanghai) Co., Ltd.

[0101] Example 1

[0102] This embodiment provides a solid acid catalyst and a preparation method thereof, the steps are as follows:

[0103] Step 1: Preparation of tin-doped molecular sieve carrier

[0104] Prepare 3 portions of 3000g of tin salt aqueous solution, each of which includes 0.2mol / L stannous sulfate and 0.1mol / L stannous chloride. At 20°C, 1000g of 4A molecular sieve is immersed in 3 portions of tin salt aqueous solution, each immersion time is 5h. During this process, tin ions enter the 4A molecular sieve. After taking out the 4A molecular sieve from the last portion of the tin salt aqueous solution, wash it twice with 5000g of deionized water at 20°C, each time for 1h, put it in a vacuum oven, bake it at a pressure of 10kPaA, a baking temperature of 90°C, and a baking time of 10h, and then put it in a roasting furnace for roasting, the roasting temperature is 300°C, the roasting pressure is 90kPaA, and the roasting time is 5h, to obtain a tin-doped molecular sieve carrier.

[0105] The mass percentage of tin element in the tin-doped molecular sieve carrier was measured to be 4.5%, the specific surface area was 522m² / g, and the pore size was 0.38μm.

[0106] Step 2: Preparation of powder catalyst

[0107] 1000g of the tin-doped molecular sieve carrier obtained in step (1) is added to 3000g of a mixed aqueous solution of ammonium molybdate and ammonium silicate, wherein the concentration of ammonium molybdate is 0.2mol / L and the concentration of ammonium silicate is 0.2mol / L. The mixture is stirred and mixed at 80°C for 10h to obtain a mixed system, and the temperature is lowered to 20°C. Dilute sulfuric acid is added to the mixed system until the pH value of the mixed system is 1, and molybdenum silicate is generated by reaction. After reacting for 6h, the filter cake is obtained by suction filtration at 20kPaA, and is placed in a vacuum oven at a baking pressure of 10kPaA, a baking temperature of 80°C, and a baking time of 12h. The filter cake is then placed in a calcining furnace for calcination at a baking temperature of 300°C, a baking pressure of 90kPaA, and a baking time of 5h to obtain a powder catalyst.

[0108] Step 3: Preparation of solid acid catalyst

[0109] 1000 g of the powder catalyst obtained in step (2), 200 g of pseudo-boehmite, 20 g of silica sol, 20 g of aluminum sol and 400 g of 25 wt% dilute sulfuric acid were mixed and stirred evenly, added to a granulator and processed into spheres, and then placed in a calcining furnace for calcination at a calcination temperature of 400° C., a calcination pressure of 90 kPaA, and a calcination time of 4 h to obtain a spherical solid acid catalyst.

[0110] The content of silicomolybdic acid in the solid acid catalyst was measured to be 13.2 wt %, the content of sulfuric acid was 6.2 wt %, and the average particle size was 3.5 mm.

[0111] Example 2

[0112] This embodiment provides a solid acid catalyst and a preparation method thereof, the steps are as follows:

[0113] Step 1: Preparation of tin-doped molecular sieve carrier

[0114] Prepare 5 portions of 3000g of tin salt aqueous solution, each of which includes 0.3mol / L stannous sulfate and 0.1mol / L stannous chloride. At 30°C, 1000g of 4A molecular sieve is immersed in 5 portions of tin salt aqueous solution, each immersion time is 8h. During this process, tin ions enter the 4A molecular sieve. After taking out the 4A molecular sieve from the last portion of the tin salt aqueous solution, wash it twice with 5000g of deionized water at 20°C, each time for 1h, put it in a vacuum oven, bake it at a pressure of 10kPaA, a baking temperature of 90°C, and a baking time of 10h, and then put it in a roasting furnace for roasting, the roasting temperature is 400°C, the roasting pressure is 95kPaA, and the roasting time is 10h, to obtain a tin-doped molecular sieve carrier.

[0115] The mass percentage of tin element in the tin-doped molecular sieve carrier was measured to be 4.9%, the specific surface area was 539m² / g, and the pore size was 0.36μm.

[0116] Step 2: Preparation of powder catalyst

[0117] 1000g of the tin-doped molecular sieve carrier obtained in step (1) is added to a mixed aqueous solution of 3000g of ammonium molybdate and ammonium silicate, wherein the concentration of ammonium molybdate is 0.24mol / L and the concentration of ammonium silicate is 0.2mol / L. The mixture is stirred and mixed at 90°C for 15h to obtain a mixed system, and the temperature is lowered to 30°C. Dilute sulfuric acid is added to the mixed system until the pH value of the mixed system is 2, and molybdenum silicate is generated by reaction. After reacting for 5h, the filter cake is obtained by suction filtration at 20kPaA, and is placed in a vacuum oven at a baking pressure of 10kPaA, a baking temperature of 80°C, and a baking time of 12h. Then, the filter cake is placed in a calcining furnace for calcination at a baking temperature of 400°C, a baking pressure of 95kPaA, and a baking time of 10h to obtain a powder catalyst.

[0118] Step 3: Preparation of solid acid catalyst

[0119] 1000 g of the powder catalyst obtained in step (2), 200 g of pseudo-boehmite, 20 g of silica sol, 20 g of aluminum sol and 400 g of 25 wt% dilute sulfuric acid were mixed and stirred evenly, added to a granulator and processed into spheres, and then placed in a calcining furnace for calcination at a calcination temperature of 500° C., a calcination pressure of 95 kPaA, and a calcination time of 8 h to obtain a spherical solid acid catalyst.

[0120] The content of silicomolybdic acid in the solid acid catalyst was measured to be 13.9 wt %, the content of sulfuric acid was 6.5 wt %, and the average particle size was 4.2 mm.

[0121] Example 3

[0122] This embodiment provides a solid acid catalyst and a preparation method thereof, the steps are as follows:

[0123] Step 1: Preparation of tin-doped molecular sieve carrier

[0124] Prepare 4 portions of 3000g of tin salt aqueous solution, each of which includes 0.25mol / L stannous sulfate and 0.1mol / L stannous chloride. At 30°C, 1000g of 4A molecular sieve is immersed in 4 portions of tin salt aqueous solution, each immersion time is 6h. During this process, tin ions enter the 4A molecular sieve. After taking out the 4A molecular sieve from the last portion of the tin salt aqueous solution, wash it twice with 5000g of deionized water at 20°C, each time for 1h, put it in a vacuum oven, bake it at a pressure of 10kPaA, a baking temperature of 90°C, and a baking time of 10h, and then put it in a roasting furnace for roasting, the roasting temperature is 350°C, the roasting pressure is 95kPaA, and the roasting time is 10h, to obtain a tin-doped molecular sieve carrier.

[0125] The mass percentage of tin element in the tin-doped molecular sieve carrier was measured to be 4.4%, the specific surface area was 501m² / g, and the pore size was 0.37μm.

[0126] Step 2: Preparation of powder catalyst

[0127] 1000g of the tin-doped molecular sieve carrier obtained in step (1) is added to a mixed aqueous solution of 3000g of ammonium molybdate and ammonium silicate, wherein the concentration of ammonium molybdate is 0.22mol / L and the concentration of ammonium silicate is 0.2mol / L. The mixture is stirred and mixed at 80°C for 15h to obtain a mixed system, and the temperature is lowered to 30°C. Dilute sulfuric acid is added to the mixed system until the pH value of the mixed system is 3, and molybdenum silicate is generated by reaction. After reacting for 7h, the filter cake is obtained by suction filtration at 20kPaA, and is placed in a vacuum oven at a baking pressure of 10kPaA, a baking temperature of 80°C, and a baking time of 12h. Then, the filter cake is placed in a calcining furnace for calcination at a baking temperature of 350°C, a baking pressure of 90kPaA, and a baking time of 8h to obtain a powder catalyst.

[0128] Step 3: Preparation of solid acid catalyst

[0129] 1000 g of the powder catalyst obtained in step (2), 100 g of pseudo-boehmite, 10 g of silica sol, 10 g of aluminum sol and 200 g of 25 wt% dilute sulfuric acid were mixed and stirred uniformly, added to a granulator and processed into spheres, and then placed in a calcining furnace for calcination at a calcination temperature of 500° C., a calcination pressure of 95 kPaA, and a calcination time of 8 h to obtain a spherical solid acid catalyst.

[0130] The content of silicomolybdic acid in the solid acid catalyst was measured to be 13.9 wt %, the content of sulfuric acid was 6.4 wt %, and the average particle size was 3.7 mm.

[0131] Comparative Example 1

[0132] This comparative example provides a solid acid catalyst and a preparation method thereof, which are basically the same as Example 1, except that tin is not added to the molecular sieve carrier, and when preparing the powder catalyst, 1000g of 4A molecular sieve is directly added to a mixed aqueous solution of 3000g of ammonium molybdate and ammonium silicate.

[0133] Comparative Example 2

[0134] This comparative example provides a solid acid catalyst and a preparation method thereof, which is basically the same as Example 1, except that the acid supported by the tin-doped molecular sieve carrier is phosphotungstic acid and sulfuric acid, and step 2 is specifically as follows:

[0135] Step 2: Preparation of powder catalyst

[0136] 1000g of the tin-doped molecular sieve carrier obtained in step (1) is added to a mixed aqueous solution of 3000g of ammonium phosphate and ammonium tungstate, wherein the concentration of ammonium phosphate is 0.2mol / L and the concentration of ammonium tungstate is 0.2mol / L. The mixture is stirred and mixed at 80°C for 10h to obtain a mixed system, and the temperature is lowered to 20°C. Dilute sulfuric acid is added to the mixed system until the pH value of the mixed system is 1, and phosphotungstic acid is generated by reaction. After reacting for 6h, the filter cake is obtained by suction filtration at 20kPaA, and is placed in a vacuum oven at a baking pressure of 10kPaA, a baking temperature of 80°C, and a baking time of 12h. Then, the filter cake is placed in a calcining furnace for calcination at a baking temperature of 300°C, a baking pressure of 90kPaA, and a baking time of 5h to obtain a powder catalyst.

[0137] Comparative Example 3

[0138] This comparative example provides a solid acid catalyst and a preparation method thereof, which is basically the same as Example 1, except that sulfuric acid is not added during bonding and forming, and step 3 is specifically as follows:

[0139] Step 3: Preparation of solid acid catalyst

[0140] 1000 g of the powder catalyst obtained in step (2), 200 g of pseudo-boehmite, 20 g of silica sol and 20 g of aluminum sol are mixed and stirred evenly, added to a granulator and processed into spheres, and then placed in a calcining furnace for calcination at a calcination temperature of 400° C., a calcination pressure of 90 kPaA and a calcination time of 4 h to obtain a spherical solid acid catalyst.

[0141] Example 4-Example 8

[0142] Embodiment 4-embodiment 8 provides a kind of 4-hydroxybutyl acrylate and preparation method thereof, and the steps are as follows:

[0143] The solid acid catalyst prepared in Example 1 was loaded into Figure 1The reaction distillation tower 10 of the reaction device shown in the figure is used. The polymerization inhibitor ZJ-709 is added to acrylic acid to prepare an acrylic acid solution, which is then fed into the reaction distillation tower 10 from the first feed port 11. The gaseous tetrahydrofuran is fed into the reaction distillation tower 10 from the second feed port 12. The ratio of acrylic acid to the polymerization inhibitor 709 and the ratio of acrylic acid to tetrahydrofuran in Examples 4 to 8 are shown in Table 1.

[0144] Nitrogen was introduced into the reaction distillation tower to control the top pressure at 0.1 MPaG, the oil bath temperature was adjusted to maintain the top temperature at 90°C, the pressure of the short-path evaporator was 1 kPaA, and the oil bath temperature was 80°C to prepare 4-hydroxybutyl acrylate of Examples 4 to 8.

[0145] The conversion rate of tetrahydrofuran, the selectivity of polytetrahydrofuran and the selectivity of 4-hydroxybutyl acrylate of each example were calculated. The results are shown in Table 1.

[0146] Table 1

[0147]

[0148] It can be seen that when the solid acid catalyst is prepared by using Example 1, the conversion rate of tetrahydrofuran is greater than 99%, the selectivity of the by-product polytetrahydrofuran is less than 2%, and the selectivity of the product 4-hydroxybutyl acrylate is greater than 98%.

[0149] Example 9-Example 13

[0150] Embodiment 9-embodiment 13 provides a kind of 4-hydroxybutyl acrylate and preparation method thereof, and the steps are as follows:

[0151] The solid acid catalyst prepared in Example 2 was loaded into Figure 1 The reaction distillation tower 10 of the reaction device shown in the figure is used. The polymerization inhibitor ZJ-709 is added to acrylic acid to prepare an acrylic acid solution, which is then fed into the reaction distillation tower 10 from the first feed port 11. The gaseous tetrahydrofuran is fed into the reaction distillation tower 10 from the second feed port 12. The ratio of acrylic acid to 709 polymerization inhibitor and the ratio of acrylic acid to tetrahydrofuran in Examples 9 to 13 are shown in Table 2.

[0152] Nitrogen was introduced into the reaction distillation tower to control the top pressure at 0.2 MPaG, the oil bath temperature was adjusted to maintain the top temperature at 100°C, the pressure of the short-path evaporator was 2 kPaA, and the oil bath temperature was 105°C to prepare 4-hydroxybutyl acrylate of Examples 9 to 13.

[0153] The conversion rate of tetrahydrofuran, the selectivity of polytetrahydrofuran and the selectivity of 4-hydroxybutyl acrylate of each example were calculated. The results are shown in Table 2.

[0154] Table 2

[0155]

[0156] It can be seen that when the solid acid catalyst is prepared by using Example 2, the conversion rate of tetrahydrofuran is greater than 99%, the selectivity of the by-product polytetrahydrofuran is less than 2%, and the selectivity of the product 4-hydroxybutyl acrylate is greater than 98%.

[0157] Example 14-Example 18

[0158] Example 14-Example 18 provides a 2-methacrylate-4-hydroxybutyl ester and a preparation method thereof, the steps are as follows:

[0159] The solid acid catalyst prepared in Example 3 was loaded into Figure 1 The reaction distillation tower 10 of the reaction device shown in the figure is used. ZJ-709 polymerization inhibitor is added to 2-methylacrylic acid to prepare an acrylic acid solution, which is then fed from the first feed port 11 of the reaction distillation tower 10. Gaseous tetrahydrofuran is fed from the second feed port 12 of the reaction distillation tower 10. The ratio of acrylic acid to 709 polymerization inhibitor and the ratio of acrylic acid to tetrahydrofuran in Examples 14 to 18 are shown in Table 3.

[0160] Nitrogen was introduced into the reaction distillation tower to control the top pressure at 0.1 MPaG, and the oil bath temperature was adjusted to maintain the top temperature at 90°C. The pressure of the short-path evaporator was 2 kPaA, and the oil bath temperature was 120°C to prepare 4-hydroxybutyl acrylate of Examples 14 to 18.

[0161] The conversion rate of tetrahydrofuran, the selectivity of polytetrahydrofuran and the selectivity of 4-hydroxybutyl acrylate of each example were calculated. The results are shown in Table 3.

[0162] Table 3

[0163]

[0164] It can be seen that when the solid acid catalyst is prepared by using Example 3, the conversion rate of tetrahydrofuran is greater than 99%, the selectivity of the by-product polytetrahydrofuran is less than 2%, and the selectivity of the product 2-methacrylate-4-hydroxybutyl ester is greater than 98%.

[0165] Comparative Example 4-Comparative Example 6

[0166] Comparative Examples 4 to 6 provide 4-hydroxybutyl acrylate and a preparation method thereof, which are basically the same as Example 4, except that the solid catalyst of Example 1 is replaced by the solid catalyst prepared by Comparative Examples 1 to 3, respectively. The conversion rate of tetrahydrofuran, the selectivity of polytetrahydrofuran and the selectivity of 4-hydroxybutyl acrylate of each comparative example are calculated, and the results are shown in Table 4.

[0167] Table 4

[0168]

[0169] Embodiment 19

[0170] This embodiment provides 4-hydroxybutyl acrylate and a preparation method thereof, which is basically the same as that of Embodiment 4, except that tetrahydrofuran is in liquid state, and the steps are as follows:

[0171] The solid acid catalyst prepared in Example 1, liquid tetrahydrofuran and ZJ-709 polymerization inhibitor were added to acrylic acid to prepare an acrylic acid solution, which was added into a kettle reactor. The pressure in the reactor was 0.1 MPaG, the temperature of the reaction liquid was 105° C., the stirring speed was 300 rpm, and the reaction time was 2 h to prepare 4-hydroxybutyl acrylate.

[0172] The calculated conversion rate of tetrahydrofuran was 94.2%, the selectivity of polytetrahydrofuran was 9.7%, and the selectivity of 4-hydroxybutyl acrylate was 90.3%. Compared with Example 4, it can be seen that liquid tetrahydrofuran affects the product selectivity to a certain extent.

[0173] Comparative Example 7

[0174] This comparative example provides 4-hydroxybutyl acrylate and a preparation method thereof, which are basically the same as Example 4, except that the filler in the reaction distillation tower 10 is replaced by a strong acid cation exchange resin with a brand of A45 instead of the solid acid catalyst in Example 1.

[0175] The calculated conversion rate of tetrahydrofuran is 99.0%, the selectivity of polytetrahydrofuran is 12.2%, and the selectivity of 4-hydroxybutyl acrylate is 87.8%. It can be seen that compared with the strong acid cation exchange resin, the solid acid catalyst has a better catalytic effect, a higher conversion rate of tetrahydrofuran, less self-polymerization of tetrahydrofuran, and a higher selectivity of 4-hydroxybutyl acrylate.

[0176] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0177] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A solid acid catalyst, characterized in that The invention comprises a bonding material, a tin-doped molecular sieve carrier and an acid. The tin-doped molecular sieve carrier is dispersed in the bonding material and loaded with an acid. The acid comprises silicomolybdic acid and an inorganic acid.

2. The solid acid catalyst according to claim 1, characterized in that Includes at least one of the following features: (1) The mass percentage of the silicomolybdic acid in the solid acid catalyst is 10wt% to 50wt%; preferably 25wt% to 40wt%; (2) The mass percentage of the inorganic acid in the solid acid catalyst is 3wt% to 10wt%; (3) The inorganic acid includes one or more of nitric acid, hydrochloric acid, sulfuric acid and phosphoric acid; preferably, the inorganic acid includes sulfuric acid.

3. The solid acid catalyst according to claim 1, characterized in that The average particle size of the solid acid catalyst is 3 mm to 5 mm.

4. The solid acid catalyst according to any one of claims 1 and 3, characterized in that Includes at least one of the following features: (1) The mass percentage of tin element in the tin-doped molecular sieve carrier is 3% to 8%, preferably 4% to 5%; (2) The specific surface area of ​​the tin-doped molecular sieve carrier is 300 m 2 / g~600m 2 / g; (3) The pore size of the tin-doped molecular sieve carrier is 0.3 μm to 0.5 μm.

5. The solid acid catalyst according to claim 4, characterized in that The preparation method of the tin-doped molecular sieve carrier comprises the following steps: Mixing molecular sieve, water-soluble tin salt and water to allow tin ions to enter the molecular sieve, and collecting the solid for a first calcination treatment; Optionally, mixing a molecular sieve, a water-soluble tin salt and water to allow tin ions to enter the molecular sieve comprises the following steps: dissolving the water-soluble tin salt in the water to obtain a plurality of tin salt solutions; immersing the molecular sieve in the plurality of tin salt solutions respectively; optionally, the number of the tin salt solutions is 3 to 5; optionally, the total immersion time of the molecular sieve in the tin salt solution is 15 hours to 40 hours; optionally, the ambient temperature of the immersion of the molecular sieve in the tin salt solution is 20° C. to 30° C.; Optionally, the molecular sieve is 4A molecular sieve; Optionally, the water-soluble tin salt includes one or more of stannous sulfate and stannous chloride; Optionally, the tin salt includes stannous sulfate and stannous chloride; Optionally, the molar ratio of the stannous sulfate to the stannous chloride is (1-4):1; Optionally, the temperature of the first calcination treatment is 300° C. to 400° C.; Optionally, the pressure of the first calcination treatment is 90 kPaA-95 kPaA; Optionally, the first calcination treatment is performed for 5 h to 10 h.

6. A method for preparing the solid acid catalyst according to any one of claims 1 to 5, characterized in that: The following steps are involved: loading silicomolybdic acid onto the tin-doped molecular sieve carrier to obtain a powder catalyst; The powder catalyst, binder and inorganic acid are mixed, and after forming, a third calcination treatment is performed.

7. The method for preparing a solid acid catalyst according to claim 6, characterized in that: Loading silicomolybdic acid onto the tin-doped molecular sieve carrier comprises the following steps: Mixing the tin-doped molecular sieve carrier, ammonium molybdate, ammonium silicate and water, stirring to obtain a mixed system; Adjusting the pH value of the mixed system to react and generate the molybdenum silicate, and collecting the solid for a second calcination treatment; Optionally, the ratio of the mass of the tin-doped molecular sieve carrier to the sum of the masses of the ammonium molybdate and the ammonium silicate is 1:(300-400); Optionally, the molar ratio of ammonium molybdate to ammonium silicate is (1-2):1; preferably (1-1.2):1; Optionally, the temperature of the mixed system is adjusted to a pH value of 1 to 3; Optionally, the method for adjusting the temperature of the mixed system to a pH value comprises: adding an inorganic acid to the mixed system; Optionally, the inorganic acid comprises one or more of nitric acid, hydrochloric acid, sulfuric acid and phosphoric acid; Optionally, the stirring temperature is 80°C to 90°C; Optionally, the stirring time is 10h~15h; Optionally, the reaction temperature is 20°C to 30°C; Optionally, the reaction time is 4h~8h; Optionally, the temperature of the second calcination treatment is 300° C. to 400° C.; Optionally, the pressure of the second calcination treatment is 90 kPaA~95 kPaA; Optionally, the second calcination treatment time is 5h~10h.

8. The method for preparing a solid acid catalyst according to claim 6, characterized in that: Includes at least one of the following features: (1) The binder includes one or more of pseudo-boehmite, silica sol and alumina sol; optionally, the binder includes pseudo-boehmite, silica sol and alumina sol, and the mass ratio of the pseudo-boehmite, silica sol and alumina sol is (8-10): (0.5-1.5): (0.5-1.5); (2) The mass ratio of the powder catalyst, the binder and the sulfuric acid is (10-20): (1.5-4): (0.8-1.2); (3) The average particle size of the intermediate product obtained by molding is 3mm~5mm; (4) The temperature of the third calcination treatment is 400°C to 500°C; (5) The pressure of the third calcination treatment is 90 kPaA~95 kPaA; (6) The third calcination treatment is performed for 4 to 8 hours.

9. A method for preparing a hydroxybutyl acrylate compound, characterized in that: The following steps are involved: In the presence of a solid acid catalyst according to any one of claims 1 to 5, a ring-opening addition reaction is carried out between an acrylic acid compound and tetrahydrofuran to generate the hydroxybutyl acrylate compound; Optionally, the tetrahydrofuran participates in the ring-opening addition reaction in a gaseous state; Optionally, the molar ratio of the acrylic acid compound to tetrahydrofuran is (1-3):1; preferably (1.1-1.5):1; Optionally, the acrylic compound is selected from one or more of acrylic acid and 2-methyl methacrylate; Optionally, the ring-opening addition reaction is also carried out in the presence of a polymerization inhibitor; optionally, the mass ratio of the polymerization inhibitor to the acrylic compound is (0.001-0.005):1; preferably (0.002-0.003):

1.

10. A hydroxybutyl acrylate compound, characterized in that: It is prepared by the preparation method described in claim 9.

Citation Information

Cited By

  • Synthesis method and application of composite modified Y-type molecular sieve

    CN120097358A